What Do Malaysians Think of America and Its Foreign Policy Post 9/11? - Mustafa, Hasrina; Ahmad, Jamilah; Nordin, Mohammad Zin (Taylor & Francis, 2008)
The study aims to understand the overall perceptions among Malaysians concerning America in the aftermath of the September 11 attacks, with a special focus on the Gulf issues, i.e. the issue of terrorism, the issue of Israel versus Palestine and Lebanon, the issue of Iraq and the issue of Iran’s nuclear-arms programme. Both quantitative and qualitative research methods were used in the study. Results of the quantitative analysis express a prominent difference between Malays and other races on every issue, with Malays having less liberal perceptions towards America than other races. The results show that most participants do not blame the American people but put the responsibility on the American government. The qualitative analysis reveals that media does influence the perceptions of the participants towards America. It also illustrates that the participants are aware and discontented with the issues that are going on in Gulf countries. The overall research findings strongly indicate that the Malaysian perception towards the American government and its foreign policy are currently unfavourable.